TỔ CHỨC XÃ HỘI VÀ SỰ CỐ KẾT CỘNG ĐỒNG TRONG SỬ THI XƠ ĐĂNG - Lê, Ngọc Bính (Trường Đại học Đà Lạt, 2023)
The Xo-Dang epic contains a lot of content such as history, society, culture, etc of the Xo-Dang people. This article will highlight the social organization characteristics and solid community cohesion reflected in the epics of this ethnic group.